Pelatihan Strategi Pemasaran di Era New Normal pada Kalangan Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Bumigora - Rini Anggriani; Abdurrahman Abdurrahman; Isra Dewi Kuntary Ibrahim (LPPM Universitas Bumigora, 2021)
The purpose of this training is to increase the knowledge of students during “new normal” era through training on sustainable marketing strategies. They are expected to survive and to produce product or service competitiveness that is able to compete in competitive competition. In addition, training is carried out to provide added value and increases various marketing mixed strategies which include 4P’s (Product, Place, Price, and Promotion). The method of implementing this service program is carried out by early identification of students who are related to the problems and obstacles faced by students. Therefore, both parties carry out the program in three steps which are preparation of materials, training or socialization, and recommendations.